Phytochemical Profiling of Passiflora edulis Vines - Odion, Emmanuel Eimiomodebheki; Nwigwe, Godfavour Nzubechukwu; Ambe, Daniel Akpe-Efiak; Nnamani, Monica Nnenna; Osigwe, Chinyelu Clementina; Odiete, Eravweroso Congrat; Iyanyi, Loveth Uchechukwu (Sciences of Phytochemistry, 2024)
Over time Passiflora edulis f. flavicarpa (PEFF) have been utilized in traditional medicine for the treatment of different health ailments. This study aims to identify the phytochemical constituents in the vines of PEFF responsible for its traditional usage. Maceration in methanol was used in the extraction of the powdered vines and standard procedures were also used to screen for its phytochemical contents. Two chromatographic techniques such as High Pressure Liquid Chromatography (HPLC) and Gas Chromatography - Mass Spectrometry (GC-MS) were exploited to identify and quantify the phytoconstituents in the methanol extract. Phytochemical screening showed alkaloids, glycosides, flavonoids, tannins, steroids, saponins and terpenoids in the vines of PEFF. Prominent compound revealed by HPLC analysis include pyrogallol (18.64%), ferulic acid (13.71%), ellagic acid (12.88%), salicylic acid (10.83%), ribalinidine (10.50%) and cresol (9.67%). While the GC-MS analysis showed Octadec-9-enoic acid (67.78%); 3-methylindole-2-carboxlic acid,4,5,6,7-tetrahydro-, ethyl ester (16.89%) and 3-aminopyrrolidine (14.52%). Thus, the vines of PEFF contain phytoconstituents responsible for it use in traditional medicine.